PENGARUH ABU VOLKAN DARI BERBAGAI KETINGGIAN TEMPAT, PUPUK FOSFAT, DAN ZEOLIT TERHADAP PERTUMBUHAN DAN KUALITAS HASIL SAMBILOTO (Andrographis paniculata Ness.) - , latifa nuraini ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Sambiloto a medicinal plant that contains many benefits for health. The need for raw materials from pharmaceutical industry increasingly bitter plant but its availability is limited. Growth and yield quality of the content of bioactive bitter plant can be improved by making use of volcanic ash soil as a growing medium. Volcanic ash soil containing mineral nutrients that are very complex and so potentially increase the growth and yield quality of bitter plant. The study aims to determined the influence of volcanic ash growing media application of phosphate fertilizer, and zeolite on growth and yield bitter plant, and to determine the effect of interaction between volcanic ash soil from some altitude, phosphate fertilizer, and zeolite to elevated levels of andrographolide bitter plant. The study used a randomized block design factorial 3 factors (3 x 4 x 2). The first factor is the altitude of volcanic ash soil from 3 places of origin (V), consists of 3 levels of height 100, 400, and 800 m above sea level. The second factor was fertilization fertilizer dose of SP-36 (P), consisting of 4 levels : 0, 75, 150, and 225 kg ha-1. The third factor is a measure of zeolite (Z), consisting of 2 levels : 0 kg ha-1 and 2,000 kg ha-1. The results showed that the origin of ash Volkan altitude 800 m above sea level and SP-36 fertilizer at 75 kg ha-1 gave the best effect on the growth of plant height bitter. Origin of ash Volkan altitude 400 m above sea level gives the best effect on the growth of branches. SP-36 interactions fertilization of 150 kg ha-1 with the provision of zeolite up to 2,000 kg ha-1 gave the best effect on the growth of plant leaves bitter. Interaction Volkan ash origin of altitude 800 m above sea level with P fertilizer at 75 kg ha-1 of SP-36 gives the best effect on the growth of stem diameter bitter crop. The altitude of origin Volkan ash that gives the best effect on total plant dry weight is 400 m asl bitter. The ratio of root to canopy and harvest index that gives the best effect is the interaction Volkan ash from an altitude of 400 m above sea level with SP-36 fertilizer of 150 kg ha-1 and the provision of zeolites as many as 2,000 kg ha-1. Growth and yield of total dry weight, low crown root ratio with a high harvest index, as well as increased content of andrographolide can be achieved in the cultivation of bitter plant that uses volcanic ash soil media from a height of 400 m above sea level home with SP-36 fertilizer application of 75 kg ha-1 without zeolites.